Chemoenzymatic Total Synthesis of (+)-Oxycodone from Phenethyl Acetate - Endoma-Arias, Mary Ann A.; Makarova, Mariia; Dela Paz, Helen E.; Hudlicky, Tomas (Synthesis, 2019)
The stereoselective total synthesis of unnatural (+)-oxycodone from phenethyl acetate is described. Absolute stereochemistry was established via microbial dihydroxylation of phenethyl acetate with the recombinant strain JM109 (pDTG601A) to the corresponding cis-cyclohexadienediol whose configuration provides for the absolute stereochemistry of the ring C of (+)-oxycodone. Intramolecular Heck cyclization was employed to establish the quaternary carbon at C-13, along with the dibenzodihydrofuran functionality. The C-14 hydroxyl was installed via SmI2-mediated radical cyclization. The synthesis of (+)-oxycodone was completed in a total of 13 steps and an overall yield of 1.5%. Experimental and spectral data are provided for all new compounds.
Keywords: enzymatic dihydroxylation; total synthesis; oxycodone; Parker’s hydroamination; pinacol-type coupling